A Theoretical Perspective on European Migration History: From the Securitization Paradigm to the Postcolonial Orientation (Third Sector Social Economic Review, 2025)
The study of European migration history and migration theories is essential for understanding the multidimensional nature of contemporary mobility. While classical approaches long emphasized economic factors and individual choices, current migration patterns are far too complex to be explained within such limited frameworks. Within the European Union, the increasingly dominant paradigm of securitization often frames migrants primarily as a threat, leading to the militarization of borders, the proliferation of exclusionary policies, and the marginalization of the humanitarian dimension of migration.This research highlights the critical perspective offered by the post‑colonial approach. Post‑colonial theory stresses the need to contextualize migration within historical continuities and inequalities inherited from colonialism. Migration from former colonies to Europe cannot be understood merely as an economic choice; rather, it reflects the enduring effects of Europe’s colonial past. This perspective allows migration to be assessed through the lenses of global injustices, identity struggles, and cultural hybridity, offering a more comprehensive understanding of mobility.In conclusion, the study argues that European migration policies should not be confined to security‑centered strategies but must also incorporate historical and critical awareness, paving the way for frameworks that are more inclusive, equitable, and human‑centered.